Formation of Research Competence of Students by Means of Mobile Education - Galustyan, Olga Vladimirovna; Borozdin, Sergey Alexandrovich; Pleshakov, Maxim Aleksandrovich; Askhadullina, Nailya Nurgayanovna; Radchenko, Lidia Alekseevna (International Journal of Interactive Mobile Technologies (iJIM), 2020)
The article outlines the need of reforming the higher education system, which should be aimed at educating graduates who are able to coordinate their future professional activities independently by means of mobile education. The authors conclude that this is impossible without the formation of research competence of students during their studies at the university. One of the main tasks of higher education is not only to present information to students, but to form the ability to obtain it independently, to be able to process it and to look for non-standard solutions. Motivational, communicative, reflexive, personal components within the structure of research competence are revealed in the article. The results of experimental work of formation of research competence of students by means of mobile education are presented. The authors conclude that educational activity becomes more continuous and motivated within formation of research competence of students by means of mobile education.